E-Inventory Information System at PT. Resik Nyaman Sejahtera - Yudi, Yudi; Indriani, Karlena; Ramanda, Kresna (Sinkron : jurnal dan penelitian teknik informatika, 2019)
E-Inventory Information System at PT. Resik Nyaman Sejahtera. PT. Resik Nyaman Sejahtera is a company engaged in cleaning services that serve cleaning at apartments / hotels, restaurants, hospitals, universities, schools, supermarkets, villas, factories, offices, government offices or national private and other places. Constraints faced by PT. Resik Nyaman Sejahtera in carrying out existing projects is still using the manual process in inventorying / stocking of goods in and out of the warehouse so that it is difficult to find data and control the in and out of inventory / stock of goods in warehouses for ongoing projects or those that have been finished. Because of that the author proposes a intranet web-based e-inventory application that is made to overcome and minimize the problem. Broadly speaking, the application designed or developed consists of the process of recording data of goods, goods entering and leaving the warehouse, inventory of goods, and inventory reports. The results of this study produce an e-inventory application system that provides convenience for warehouse staff and administrators to manage and control inventory in the warehouse